2005
DOI: 10.1016/j.cardiores.2004.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of PPAR-? ligands in ischemia?reperfusion injury, inflammation and shock

Abstract: Peroxisome proliferator-activated receptor-gamma (PPAR-gamma) is a ligand-activated transcription factor belonging to the nuclear hormone receptor superfamily. PPAR-gamma regulates gene expression by forming a heterodimer with the retinoid X receptor (RXR) before binding to sequence-specific PPAR response elements (PPREs) in the promoter region of target genes, thereby regulating several metabolic pathways, including lipid biosynthesis and glucose metabolism. Thiazolidinediones (TZDs, i.e. rosiglitazone, piogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(150 citation statements)
references
References 83 publications
6
142
0
2
Order By: Relevance
“…It has recently become evident that the therapeutic effects of TZDs reach far beyond use as insulin sensitizers. Recently, several lines of evidence have suggested that TZDs protect the heart and other organs against tissue damage caused by I/R injury (2). I/R has been shown to activate the pro-survival kinase signaling cascades, p42/p44 extracellular signal-regulated kinases (ERK1/2), which have been implicated in cell survival through recruitment of antiapoptotic pathways of protection (3).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently become evident that the therapeutic effects of TZDs reach far beyond use as insulin sensitizers. Recently, several lines of evidence have suggested that TZDs protect the heart and other organs against tissue damage caused by I/R injury (2). I/R has been shown to activate the pro-survival kinase signaling cascades, p42/p44 extracellular signal-regulated kinases (ERK1/2), which have been implicated in cell survival through recruitment of antiapoptotic pathways of protection (3).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In addition to targeting VSMCs, wherein they suppress proliferation and migration, MMPs production and Ang II receptor type 1 (AT1) expression, [16][17][18] PPARg agonists have recently been shown to possess anti-inflammatory and antiarteriosclerotic properties by antagonizing Ang II effects. [19][20][21] The TLR4 signaling activates mitogen-activated protein kinases and production of interferon-gamma-inducible protein 10 (IP-10), in turn activating protein kinase C (PKC) and finally resulting in the translocation of NF-kB. [22][23][24] Recent studies have revealed that the TLR4 signaling plays a central role in atherosclerosis, [25][26][27] thus providing an important link between inflammation, innate immunity and atherosclerosis.…”
mentioning
confidence: 99%
“…In addition to PPAR transactivation, stimulation of PPAR can also negatively regulate gene expression in a liganddependent manner by inhibiting the activities of other transcription factors, such as activated protein-1 (AP-1), nuclear factor-kappaB (NF-κB), nuclear factor of activated T-cells (NFAT) or signal transducer and activator of transcription (STAT) via mechanism known as ligand-dependent transrepression (Abdelrahman et al 2005). In contrast to transcriptional activation, transrepression does not involve binding of PPAR to response elements of the target genes but direct interaction with other transcription factors and co-repressors or modulation of kinase activity.…”
Section: Transcriptional Transrepressionmentioning
confidence: 99%
“…Research suggests that PPAR may exert beneficial effects by negatively regulating the expression of pro-inflammatory genes in inflammation-related diseases including myocardial ischemia/reperfusion injury (Abdelrahman et al 2005). Several mechanisms have been suggested to account for this activity including ligand-independent repression of the transcription of target genes via binding of PPAR to response element in the absence of ligands and recruitment of the co-repressor complexes (reviewed by Collino et al 2008).…”
Section: Transcriptional Transrepressionmentioning
confidence: 99%
See 1 more Smart Citation